2004
DOI: 10.2224/sbp.2004.32.7.667
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Ethnicity, and the Developmental Timing of First Sexual and Romantic Experiences

Abstract: One of the most important tasks faced by adolescents and young adults is the formation of romantic relationships. Little is known, however, about the developmental timing of early relational experiences. This study investigated the age at which an ethnically diverse sample of young adults (N = 683) experienced their very first date, love, serious relationship, kiss, and act of intercourse. Most had experienced each event by the end of high school, with first dates and kisses occurring at earlier ages than fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 11 publications
1
46
0
Order By: Relevance
“…All analyses were done separately for boys and girls because the context within which adolescents form sexual partnerships is strongly gender specific and the determinants of the timing of first sex differ between them [10,24,31,32]. All standard errors in the analysis were adjusted for any clustering that would arise due to lack of independence of adolescents from the same barangay (community).…”
Section: Discussionmentioning
confidence: 99%
“…All analyses were done separately for boys and girls because the context within which adolescents form sexual partnerships is strongly gender specific and the determinants of the timing of first sex differ between them [10,24,31,32]. All standard errors in the analysis were adjusted for any clustering that would arise due to lack of independence of adolescents from the same barangay (community).…”
Section: Discussionmentioning
confidence: 99%
“…13e16 In addition to lower sexual activity rates, Asian-American adolescents are also less likely to have ever been kissed, experienced a first date, or been involved in a serious relationship. 17 In a survey of California high school students, 27% of AsianAmericans reported lifetime sexual activity compared to 50% of non-Hispanic whites. 18 Explanations for this finding include fear of parental and peer disapproval of premarital sexual activity among AsianAmerican adolescents.…”
Section: Sexual Activitymentioning
confidence: 99%
“…Montgomery also discovered significant age differences, with older participants idealizing romantic love less than younger participants, while also reporting more romantic experiences such as dating and being in love. In contrast, a study by Regan et al (2004) of ethnically diverse college students at a large American university in the west documented that more women than men reported having ever been in love or having been kissed, although the vast majority of both men and women in their study reported having engaged in these romantic activities. This study also noted age effects centering on the age at which participants first kissed, first fell in love, and first engaged in sexual intercourse.…”
Section: Gender Age and Religiosity's Effects On Romance Attitudesmentioning
confidence: 81%